Study of Global Solar Radiation Potential and Ground Level Albedo at Benevento Italy - Poudyal, Khem N.; Daponte, Pasquale; Rapone, Serjio; Bhattari, Binod; Sapkota, BalKrishna; Kjeldstad, Berit (Journal of the Institute of Engineering, 2011)
Global solar irradiance iwas measured by a calibrated pyranometer (model LP PYRA 05 Delta Ohm ISO 9060) at about 1 meter off the roof top of building of the University of Sannio, Benevento, Italy (latitude 41°08' N longitude 14°45' E and 150.0 m ), from April to June 2010. This site is about 50.0 km north east of the Naples costal area so there are fluctuations in the local weather condition. Still, there was a significant amount of intensity in global solar irradiation found. The maximum solar radiation of about 659.47 W/m2 was found at 11:00 AM with clear sky conditions on May 2010 at Benevento, Italy. The maximum and minimum value of ground level albedo, 0.74 and 0.32, was found at 6:00 AM and 11:00 AM respectively. This indicates that the daily measured data of horizontal global solar radiation decreases with an increase in ground level albedo. Besides this, we concluded that there was a high level of fluctuation in the measured value of solar irradiance due to local weather conditions. The results of the research can be utilized for the conformation of variation of solar radiation due to wind speed, humidity and environmental pollution. This study will help to estimate the global solar irradiance potential available to solar energy systems at Benevento, where the average global soar irradiance is estimated to be about 5.0 kWh/m2. Key words: Global irradiance; Reflected irradiance; Albedo; Atmospheric pollution; Potential DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5124 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 284-290 Uploaded Date: 20 July, 2011